2017
DOI: 10.3238/arztebl.2017.0785
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia in Patients with Trauma in Emergency Medicine

Abstract: Ketamine, fentanyl, and morphine are suitable for analgesia in spontaneously breathing trauma patients. Fentanyl and ketamine have a rapid onset of action and a strong analgesic effect. Our quantitative meta-analysis revealed no evidence for the superiority of any of the three substances over the others. Suitable monitoring equipment, and expertise in emergency procedures are prerequisites for safe and effective analgesia by healthcare professionals..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 100 publications
0
19
0
7
Order By: Relevance
“… 25 Safety of opioid-based protocols is ensured by vital signs monitoring, the availability of antidotes (naloxone), bag mask ventilation, and providers’ expertise in emergency procedures. 26 Moreover, even if opioid related complications, such as nausea, vomiting, hypoxia and hypotension, are reported as very low, a two-tier emergency system guarantees medical support in case of adverse events or unmanageable pain. 7 , 27–30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 25 Safety of opioid-based protocols is ensured by vital signs monitoring, the availability of antidotes (naloxone), bag mask ventilation, and providers’ expertise in emergency procedures. 26 Moreover, even if opioid related complications, such as nausea, vomiting, hypoxia and hypotension, are reported as very low, a two-tier emergency system guarantees medical support in case of adverse events or unmanageable pain. 7 , 27–30 …”
Section: Discussionmentioning
confidence: 99%
“…25 Safety of opioid-based protocols is ensured by vital signs monitoring, the availability of antidotes (naloxone), bag mask ventilation, and providers' expertise in emergency procedures. 26 Moreover, even if opioid related complications, such as nausea, vomiting, hypoxia and hypotension, are reported as very low, a twotier emergency system guarantees medical support in case of adverse events or unmanageable pain. 7,[27][28][29][30] International experiences from other European countries such as Switzerland, Germany, and Denmark, as well as Australia and the United States, reported that paramedic or nurse analgesia projects are safe and effective, and could optimize treatment for a wider range of patients, particularly in rural and remote prehospital environments.…”
Section: Advantages Of Nurse-administered Analgesia In the Emergency Settingmentioning
confidence: 99%
“…First, several studies were excluded as they did not offer clear methodology on how ketamine's analgesic effectiveness was evaluated. Resource limitation in prehospital medicine, as well as the fact that ketamine is often the preferred option in the hemodynamically unstable patient, 42 may account for the lack of documented pain intensity and adverse event monitoring. The lack of standardized measurement of outcomes does mean that a meta-analysis could not be appropriately performed.…”
Section: Discussionmentioning
confidence: 99%
“…Während die periphere Venenverweilkanüle immer noch den Standard in der Notfallmedizin darstellt [10], hat sich bereits in den vergangenen Jahrzehnten der intraossäre Zugang in der pädiatrischen Notfallmedizin etabliert [9]. Aus dieser Erfahrung hat sich die intraossäre Injektion auch bei Erwachsenen als erfolgreich erwiesen und ist zusammen mit der intranasalen Applikation von Medikamenten zu einer vielversprechenden und häufigen Alternative geworden [3][4][5][6].…”
Section: Einfach Und Praktisch: Anlage Venöser Portsysteme In Rettungunclassified